From Diffusionism to the New Rural Extension Perspectives: Extensionist Actions in Ibitiara-Ba (Revista Brasileira Multidisciplinar, 2013)
In this essay we present a brief description about the rural extension historical process in Brazil, about diffusionism and findings from this process. Subsequently, it will be presented a new perspective of rural extension, that searches to value the traditional knowledge of local communities, to develop a better integration of extensionists and family farmers, looking for an improvement in the services of Rural Technical Assistance-RTA , aiming at the sustainability of the productive processes and at the satisfaction of the agricultors' expectation. Next, the rural extension in the Ibitiara City, Bahia, is presented, based on a selection of the activities developed by an extensionist group, of which the first author of this paper was part, between the years 2008 and 2011. The results point to the potential of rural extension practices to improve the socioeconomic conditions of family farmers, and to reduce clientelist practices by local authorities, quite common in semiarid's small towns, and to enhance the sustainable development for the region.
Keywords: Rural extension; Clientelism; Social organization.